A Two-Stage Bedside Intubation Method to Improve Success Rate of Post-pyloric Placement of Spiral Nasoenteric Tubes in Critically Ill Patients: A Multi-Center, Prospective Study - Xu, Jing; Li, Sinian; Chen, Xiangyin; Tan, Bo; Chen, Shenglong; Hu, Bei; Nie, Zhiqiang; Ye, Heng; Sun, Cheng; Chi, Ruibin; Chen, Chunbo (Frontiers in Medicine, 2022)
Backgrounds Prokinetic agents could improve the success rate of post-pyloric placement of self-propelled spiral nasoenteric tubes (NETs), and bedside blind technique might apply as a rescue therapy subsequent to spontaneous transpyloric migration failure. The objective of this study was to investigated the validity and safety of these two bedside intubation methods as a sequential procedure for post-pyloric placement of spiral NETs in critically ill patients. Methods The multicenter, prospective study was conducted in intensive care units of four tertiary hospitals (June 2020 to January 2021). Eligible patients received self-propelled spiral NET placements, promoted by prokinetic agents (Stage 1). An abdominal X-ray performed 24 h post-intubation confirmed the position of the tube tip. Patients with a failed transpyloric migration entered Stage 2, where beside blind intubation was conducted (reconfirmed by X-ray). The primary end point was the overall success rate of post-pyloric placement. Results The overall success rate of post-pyloric placement of the spiral NET was 91.1% (73.4% in the third portion of the duodenum [D3] or beyond). The total adverse event rate was 21.0%, without any serious adverse events. In Stage 1, 55.6% of participants achieved transpyloric migration, of these, 44.4% migrated to D3 or beyond. The median time from decision to intubate to the initiation of enteral nutrition (EN) was 25 h. In Stage 2, 83.0% of patients had successful post-pyloric intubation (67.9% in D3 or beyond). The median time from decision to EN initiation after the two-stage process was 36 h. Conclusions Prokinetic agents-assisted self-propelled intubation and remedial bedside blind technique as a sequential procedure for post-pyloric placement of spiral NETs were effective and safe, and this two-stage process did not affect the implementation of early EN in critically ill patients. Trial Registration Chinese Clinical Trial Registry, ChiCTR1900026381. Registered on 6 October 2019.